Effects of Long-Term Use of Compost on N2O and CO2 Fluxes in Greenhouse Vegetable Systems. (15th December 2017) - Han, Hui; Teng, Yanmin; Yang, Hefa; Li, Ji
ABSTRACT: This study was based on a long-term field trial of three different greenhouse vegetable growing systems which were started in March 2002. Fertilizer nitrogen and organic carbon inputs in three treatments in the spring of 2015 were as follows: (1) conventional system (CON): cow manure and dry chicken manure composts (about 146 kg N ha −1 and 1483 kg C ha −1 ) and urea (about 525 kg N ha −1 ); (2) low-input system (LOW): cow manure and dry chicken manure composts (about 325 kg N ha −1 and 3160 kg C ha −1 ) and urea (about 263 kg N ha −1 ); and (3) organic system (ORG): cow manure and dry chicken manure composts (about 651 kg N ha −1 and 5456 kg C ha −1 ). N2 O and CO2 fluxes were monitored in the growing season of 2015 (from March to August) using static chamber and gas chromatography techniques. Results showed that: (1) The N2 O and CO2 fluxes in three treatments all reached their peaks within 4 days and 8 days after irrigation, respectively. N2 O emissions were positively correlated with soil temperature, soil water-filled pore space (WFPS), and NO3 − -N contents, while strong association between CO2 emissions and soil temperature was observed. (2) Lower cumulative N2 O emission and direct emission factor ( p < 0.05) were observed in ORG than that from LOW and CON. (3) No significant differences of cumulative CO2 emissions were observed in three treatments, but CO2 emissions proportion of fertilizer carbon inputs and soil organic carbon stock in ORG was significantly lower ( p < 0.05).